Analyzing the SUPER A Strategy in Gojek's 'Emak Hemat' Advertisement - Gibbran Prathisara; Anang Masduki (Universitas Ahmad Dahlan, 2025)
Gojek’s digital advertising campaigns frequently gain viral traction due to their strong cultural relevance, emotional appeal, and creative narrative execution. However, limited academic studies specifically examine how the SUPER A creative strategy is applied within these campaigns to enhance audience engagement and brand perception. This study aims to analyze the implementation of the SUPER A strategy. Simple, Unexpected, Persuasive, Entertaining, Relevant, and Acceptable, in Gojek’s “Emak Hemat” advertisement, a campaign widely recognized for its humor, cultural resonance, and strong message of frugality. The research contributes to the growing body of literature on creative advertising strategies in Southeast Asia and provides practical insights for advertisers seeking effective storytelling models in the digital era. This study employs a qualitative research design using a case study approach and qualitative content analysis. Data were collected through documentation and non-participant observation of visual and textual elements in the “Emak Hemat” advertisement. The data were coded and analyzed based on the six dimensions of the SUPER A framework. The findings reveal that the advertisement successfully integrates all SUPER A elements. The narrative is simple and relatable, while unexpected comedic scenes maintain audience attention. The campaign’s persuasive messages emphasize affordability and practicality, supported by entertaining humor rooted in everyday Indonesian family life. Cultural relevance is strongly reflected in the portrayal of a frugal mother figure, and the closing tagline ensures the message remains acceptable and memorable to diverse audiences. In conclusion, the effective implementation of the SUPER A strategy strengthens Gojek’s brand positioning as a practical, economical solution for daily needs and demonstrates how culturally grounded storytelling can enhance advertising effectiveness in digital environments.